Clinical utility of the Prostate Health Index (phi) for biopsy decision management in a large group urology practice setting. Issue 1 (April 2018) - White, Jay; Shenoy, B.; Tutrone, Ronald; Karsh, Lawrence; Saltzstein, Daniel; Harmon, William; Broyles, Dennis; Roddy, Tamra; Lofaro, Lori; Paoli, Carly; Denham, Dwight; Reynolds, Mark
Abstract Background Deciding when to biopsy a man with non-suspicious DRE findings and tPSA in the 4–10 ng/ml range can be challenging, because two-thirds of such biopsies are typically found to be benign. The Prostate Health Index (phi ) exhibits significantly improved diagnostic accuracy for prostate cancer detection when compared to tPSA and %fPSA, however only one published study to date has investigated its impact on biopsy decisions in clinical practice. Methods An IRB approved observational study was conducted at four large urology group practices using a physician reported two-part questionnaire. Physician recommendations were recorded before and after receiving thephi test result. A historical control group was queried from each site's electronic medical records for eligible men who were seen by the same participating urologists prior to the implementation of thephi test in their practice. 506 men receiving aphi test were prospectively enrolled and 683 men were identified for the historical control group (withoutphi ). Biopsy and pathological findings were also recorded for both groups. Results Men receiving aphi test showed a significant reduction in biopsy procedures performed when compared to the historical control group (36.4% vs. 60.3%, respectively, P < 0.0001). Based on questionnaire responses, thephi score impacted the physician's patient management plan in 73% of cases, including biopsy deferrals when thephi score was low, and decisions to perform biopsies when thephi score indicated an intermediate or high probability of prostate cancer (phi ≥36). Conclusions phi testing significantly impacted the physician's biopsy decision for men with tPSA in the 4–10 ng/ml range and non-suspicious DRE findings. Appropriate utilization ofphi resulted in a significant reduction in biopsy procedures performed compared to historical patients seen by the same participating urologists who would have met enrollment eligibility but did not receive aphi test.